Making Evaluation Less Complex. Issue 7 (3rd September 2020) - Kaufman, Roger
Abstract: Evaluation is essential. If you do not evaluate you are "flying blind" because you do not know what to stop, what to modify, and what to continue. There is no shortage of evaluation models, frameworks, and approaches. Most are well intended while being complex to use. Additionally, most are stand‐alone and not linked to needs assessment data. This article suggests that if you do needs assessments using "need" as a gap in results, and apply at all three levels of organizational elements, a basic evaluation will provide clear and precise evaluation results.